Phosphate glasses: Via coacervation route containing CdFe2O4 nanoparticles: Structural, optical and magnetic characterization - Orives, Juliane R. [UNESP]; Viali, Wesley R. [UNESP]; Santagneli, Silvia H. [UNESP]; Afonso, Conrado R. M.; Carvalho, Maria H.; De Oliveira, Adilson J. A.; Nalin, Marcelo [UNESP] (Royal Society of Chemistry (RSC), 2018)
CdFe2O4 nanoparticles of around 3.9 nm were synthesized using the coprecipitation method and protected by a silica layer. The nanoparticles were mixed with a coacervate and transformed into phosphate glasses with 1, 4 and 8% in mass of nanoparticles by the melt-quenching method. TEM images confirm that the nanoparticles were successfully incorporated into the matrix without inducing crystallization. 31P NMR and Raman spectral analyses show that new P-O-Si bonds are formed in the glasses containing nanoparticles. The glass transition increases as a function of the nanoparticle content due to an increase in the connectivity of the phosphate glass chains. The UV-Vis spectra show bands at 415 and 520 nm assigned to Fe3+ ions and at 1025 nm, characteristic of Fe2+ ions, indicating that some of the nanoparticles dissolve during the melting process. The sample with 8% CdFe2O4 presents a paramagnetic behavior. The glasses obtained are transparent, non-hygroscopic and possess enormous thermal stability which is important for the production of optical devices.